Analisis Pengembangan Pariwisata Halal Negeri Di Atas Awan Bukit Nato Kabupaten Toraja Utara - Trisno Wardy Putra (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2021)
Background. The majority of the Toraja people embrace Christianity, some are Muslim and believe in animism or commonly called Alu To Dolok. Halal tourism, both in terms of guaranteeing halal products and in terms of places of worship, is needed to increase Muslim tourists in North Toraja Regency.Aim. This study aims to describe the analysis related to the development of halal tourism in the country above the clouds of Nato Hills, North Toraja Regency, in providing religious services and facilities for Muslim tourists.Methods. The method used in this study is a qualitative method, the characteristic of this research lies in the purpose of describing a case by understanding the meaning and symptoms, so that the data analysis used is descriptive analytical.Results. The results showed that the development of halal tourism in North Toraja Regency had experienced rejection due to public misunderstandings regarding the word halal, so the term halal tourism was replaced with Muslim-friendly tourism. The development of domestic halal tourism above the cloud has become a concern for the government, but the budget is limited so that the development of halal tourism is not running effectively and efficiently.